ANALISIS PENGARUH PEMBERIAN KOMPENSASI NON FINANSIAL TERHADAP KOMITMEN DAN KINERJA GURU SMP - Reni Oktavianti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2019)
Schools has the responsibility to organize quality education in accordance with the national objectives of education. Therefore, it takes a competent educators. One effort to increase the commitment and performance of teachers is the provision of non-financial compensation. Based on the description above, this study aimed to determine the effect of non-financial compensation to the commitment and impact on teacher’s performance. Looking at these effects that were tested either directly or indirectly through intermediate variable is the variable commitment of teachers to non-financial compensation is divided into two rewards career and social rewards. This research is an explanatory research, with survey research design. Data analysis technique used to review answering hypothetical model research singer using partial least squares (PLS) with a population of 126 teachers Term Research sample 96 teachers Taken Out of a population. Research shows that commitment has a significant influence towards teacher’s performance with t-statistic result 2.406, rewarding social influences have a significant effect against the commitment of teachers with t-statistic value and costs 3,873 teachers with t-statistic value 2,860. While career rewards has significant effect on teachers' commitment against with t-statistic values of 2.589. This is quite interesting because it should be mediated by the commitment of teachers so career rewards has particularly significant influence toward teacher’s performance. This interesting phenomenon is worth for a discussion. In addition between disposals other variables such as motivation should be a material consideration for further research review.Keywords: Leadership, Islamic boarding school culture, teacher’s motivation, quality of education.